PENGEMBANGAN USAHA MIE NYONYOR DI BALI BERBASIS BUDAYA DAN TEKNOLOGI - Dermawan Waruwu; I Putu Darmawijaya (Seminar Nasional Aplikasi Iptek (SINAPTEK), 2018)
ABSTRACTNyonyor noodle business in Abianbase Village - Bali was developed through cultural and technological value approaches. Nyonyor noodles become an alternative food menu for by consumers, besides consuming rice. The Dhyana Pura University Community Partnership Program (PKM) implementation team provided training, assistance, and equipment assistance to nyonyor noodle entrepreneurs (partners). Partners use technology tools to develop their businesses, so the process of making raw materials for noodles is faster and hygiene than before. In presenting nony nyonyor partners always pay attention to cultural values, ethics, religion, and friendliness so that consumers are more comfortable when consuming these noodles. The use of technology and the application of cultural values have the potential as a source of income for the community, both nyonyor noodle business owners, employees, gojek, chili farmers, onion farmers, chicken farmers, and so on. Thus, increasing income through the nyonyor noodle business provides inspiration to the younger generation for entrepreneurship, thereby increasing the economy and welfare of the Balinese and Indonesian people.Keywords: Development, Mie Nyonyor, Culture, Technology, BaliABSTRAKUsaha mie nyonyor di Desa Abianbase – Provinsi Bali dikembangkan melalui pendekatan nilai budaya dan teknologi. Mie nyonyor menjadi alternatif pilihan menu makanan bagi masyarakat, selain mengkonsumsi nasi. Tim pelaksana Program Kemitraan Masyarakat (PKM) Universitas Dhyana Pura memberikan pelatihan, pendampingan, dan bantuan alat kepada pengusaha mie nyonyor (mitra). Mitra menggunakan alat teknologi dalam mengembangkan usahanya, sehingga proses pembuatan bahan baku mie nyonyor lebih cepat dan hygiene dari sebelumnya. Dalam menyajikan mie nyonyor mitra selalu memperhatikan nilai-nilai budaya, etika, agama, dan keramahan agar konsumen semakin nyaman pada saat mengkonsumsi mie nyonyor tersebut. Penggunaan teknologi serta penerapan nilai budaya berpotensi sebagai sumber pendapatan masyarakat, baik pemilik usaha mie nyonyor, karyawan, gojek, petani cabai, petani bawang, peternak ayam, dan sebagainya. Dengan demikian, peningkatan pendapatan melalui usaha mie nyonyor ini memberikan inspirasi kepada generasi muda untuk berwirausaha, sehingga meningkatkan ekonomi serta kesejahteraan masyarakat Bali maupun Indonesia.Kata kunci: Pengembangan, Mie Nyonyor, Budaya, Teknologi, Bali